2020
DOI: 10.1039/d0sc04237d
|View full text |Cite
|
Sign up to set email alerts
|

Coligand role in the NHC nickel catalyzed C–F bond activation: investigations on the insertion of bis(NHC) nickel into the C–F bond of hexafluorobenzene

Abstract: A combined experimental and theoretical study on the mechanism of the C–F bond activation of C6F6 with [Ni(NHC)2] is provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 99 publications
1
35
0
Order By: Relevance
“…We recently demonstrated that NHC-assisted pathways play a crucial role in the nickel-catalysed C-F bond activation of fluorobenzenes. 51 A combined experimental and theoretical study on the mechanism of the C-F bond activation of C 6 F 6 with complexes of the type [Ni(NHC) 2 ] provided evidence that a concerted mechanism prevails for small NHCs whereas a radical mechanism prevails for large NHCs, and that NHCassistance plays an important alternative role for NHCs of both sizes. Considering the electronic features, it has to be expected that assistance of the co-ligand will become even more prominent for NHSi complexes.…”
Section: Conclusion and Outlook: Quo Vadis Nhsi ?mentioning
confidence: 99%
“…We recently demonstrated that NHC-assisted pathways play a crucial role in the nickel-catalysed C-F bond activation of fluorobenzenes. 51 A combined experimental and theoretical study on the mechanism of the C-F bond activation of C 6 F 6 with complexes of the type [Ni(NHC) 2 ] provided evidence that a concerted mechanism prevails for small NHCs whereas a radical mechanism prevails for large NHCs, and that NHCassistance plays an important alternative role for NHCs of both sizes. Considering the electronic features, it has to be expected that assistance of the co-ligand will become even more prominent for NHSi complexes.…”
Section: Conclusion and Outlook: Quo Vadis Nhsi ?mentioning
confidence: 99%
“…Thermal [58] and photocatalytic [59] C−F borylation procedures have subsequently been developed that are selective and efficient in generating fluorinated aryl pinacol boronate products. However, those C−F borylation methods were not able to generate C 6 F 5 Bpin from C 6 F 6 in any appreciable yields [55] . As these methods require the use of a strong base, protodeboronation may be responsible for the low yields.…”
Section: Synthesis Of Fluorinated Aryl Boronatesmentioning
confidence: 99%
“…Several studies have been reported regarding the development of nickel‐mediated C−F activation of arenes in stoichiometric processes [1,2,52–55] . However, effective catalytic borylations of these substrates using nickel catalysts were reported only recently by Martin et al .…”
Section: Synthesis Of Fluorinated Aryl Boronatesmentioning
confidence: 99%
“…Insightfully, the DFT calculations reveal that the C−F activation process proceeds through the NHC‐assisted pathway for both 9 a and 9 b . However, mechanistically 9 a proceeds via fluorine atom abstraction and phenyl radical formation, whereas 9 b favors concerted oxidative addition [42] . Very recently, Radius and co‐workers turned their focus from Ni to Co, i. e., the C−F activation at NHC cobalt half‐sandwich complexes of the type [CpCo(NHC)(olefin)] 10 a .…”
Section: C‐f Activation By Metal Nhc (Stoichiometric and Isolated Int...mentioning
confidence: 99%